European Union Toolkit for Ensuring Critical Raw Materials Supply - Irina Popova (Современная Европа, 2025)
In the context of global energy transition to renewable energy sources, there is a growing demand for critical raw materials needed to produce climate-neutral technologies. The European Union has no reserves of such raw materials and is dependent on supplies from third countries. In order to ensure access to the critical raw materials, the EU has developed and transformed a range of policy instruments. New instruments include the proposal to create a critical raw materials club, the Global gateway initiative, anti-coercion mechanism. The size and attractiveness of the European market, the EU's normative power and strong positions in all international forums allow it to push its interests and influence the critical raw materials supply chains. This in turn affects the global market and the interests of other countries, including Russia. Russia should develop cooperation with developing countries in the supply of critical raw materials, make efforts to develop value-added chains, and prevent the EU and G7 members from imposing their interests and conditions on the CRMs markets. In this case BRICS can serve as an important platform for cooperation.